VALUE OF POSTERO-ANTERIOR CEPHALOGRAMS IN ASSESSING FACIAL SYMMETRY - Daniela Anistoroaei; Vasilica Toma; Eduard Radu Cernei; Loredana Golovcencu; Alina Sodor; Georgeta Zegan (Romanian Society of Oral Rehabilitation, 2019)
The purpose of the study was to investigate the usefulness of postero-anterior cephalograms (PAC) as valuable supplementary means of analysis of dento-facial asymmetries. Material and method. The study was conducted using the Grummons method of 53 PACs that were achieved in patients with dento-facial asymmetry. The data obtained were statistically processed using SPSS 20.0 for Windows. Results.17.1% of patients presented unparalleled horizontal planes, 57.1% of patients have unequal areas of mandibular morphology triangles, 65.7% of the patients had maxilla-mandibular volumetric imbalance, 57.1% of patients had maxilla-mandibular asymmetry, and 62.9% of patients had linear asymmetry and 20% of patients with asymmetrical maxilla-mandibular relation. Significant statistical correlations were found between PAC and age stages, as well as Angle classes of malocclusion (p<0.05). Conclusions. PAC is useful to locate, quantify and differentiate the various forms of asymmetries. It is evident that only the confrontation with the clinical examination can lead to reliable conclusions.